Labour productivity growth in Malta: A sectoral decomposition analysis - Roberta Montebello; Jude Darmanin (Central Bank of Malta, 2021)
This paper computes sectoral contributions to real labour productivity growth in Malta during the two decades since 2000. The aim is to give an account of the sectoral developments affecting Malta's productivity growth in the twenty years since 2000, in the context of significant structural change. To this end, this study employs the exactly additive GEAD technique developed by Tang and Wang (2004), which allows for the decomposition of sectoral productivity growth into efficiency gains and resource reallocation. Real labour productivity growth in Malta averaged 1.2% between 2000 and 2019, double that registered in the euro area. This divergence in growth rates was driven by a consistently positive reallocation level effect in each of the sample subperiods, as a result of the large structural shifts and reforms that have occurred since 2000. On the other hand, the contribution of within-sector efficiency gains in Malta was below that observed in the euro area on average and was the main driver of cyclical fluctuations in Malta's productivity growth since 2000. Distortions such as government assistance and labour hoarding during recessions magnified these fluctuations. Across sectors, the results suggest that productivity developments were quite heterogenous, with services industries generally recording positive contributions to productivity growth. On the other hand, the manufacturing sector mainly registered negative contributions, as efficiency gains were offset by an outflow of resources towards other sectors.
Keywords: E24; J24; J21; O52; 330; Labour productivity growth; exactly-additive decomposition; sectoral contributions; structural changes; services; Malta; euro area